Chromosome-Level Assembly of the Southern Rock Bream (Oplegnathus fasciatus) Genome Using PacBio and Hi-C Technologies - Bai, Yulin; Gong, Jie; Zhou, Zhixiong; Li, Bijun; Zhao, Ji; Ke, Qiaozhen; Zou, Xiaoqing; Pu, Fei; Wu, Linni; Zheng, Weiqiang; Zhou, Tao; Xu, Peng (Frontiers in Genetics, 2021)
The Rock Bream (Oplegnathus fasciatus) is an economically important rocky reef fish of the Northwest Pacific Ocean. In recent years, it has been cultivated as an important edible fish in coastal areas of China. Despite its economic importance, genome-wide adaptions of domesticated O. fasciatus are largely unknown. Here we report a chromosome-level reference genome of female O. fasciatus (from the southern population in the subtropical region) using the PacBio single molecule sequencing technique (SMRT) and High-through chromosome conformation capture (Hi-C) technologies. The genome was assembled into 120 contigs with a total length of 732.95 Mb and a contig N50 length of 27.33 Mb. After chromosome-level scaffolding, 24 chromosomes with a total length of 723.22 Mb were constructed. Moreover, a total of 27,015 protein-coding genes and 5,880 ncRNAs were annotated in the reference genome. This reference genome of O. fasciatus will provide an important resource not only for basic ecological and population genetic studies but also for dissect artificial selection mechanisms in marine aquaculture.